The Enantiomeric Scaffold Approach to Highly Functionalized 1-Oxadecalines: Enantio- and Regiocontrolled [4+2] Cycloadditions of 5-Alkenyl-η(3)-Pyranylmolybenum Complexes - Arrayás, Ramón Gómez (2007)
TpMo(CO)(2)(5-alkenyl-η-2,3,4-pyranyl) diene complexes function as excellent chiral scaffolds for the efficient regio- and enantiocontrolled synthesis of highly functionalized 1-oxadecaline derivatives through a novel transition metal-mediated Diels-Alder reaction. Very good to excellent yields and excellent levels of endo-selectivity are obtained and the reaction gives products with complete retention of enantiomeric purity when carried out with chiral, non-racemic scaffolds. A subtle structural modification on the diene (replacement of an H by a trans-CH(3) group) leads to a complete change of regiochemistry, which is discussed from a mechanistic point of view. The role of the η(3)-coordinated TpMo(CO)(2) moiety is also critical to the further functionalization of the [4+2] cycloadducts, as illustrated by the preparation of 20 variously functionalized 1-oxadecaline derivatives (>98% ee when carried out with high enantiopurity scaffolds).